Role of Knowledge Management in Sport Organizations - Manev, Gjorgji; Jakimovski, Jorde (International Journal of Economic Practice and Policy, 2018)
The popularity of sport and recreation contributed to having sport facilities and sport grounds constructed throughout our whole country. It is in these facilities, fields and grounds where sport activists such as members of amateur sport clubs and professional sport clubs and sport organizations, put into practice their sport-related ideas. They have strong encouragement from their fans, political organizations, the spectators in the well equipped sport facilities, on the internet, in the information and communication technologies, from knowledge management and in the media. Knowledge management in successful sport organizations can be associated with their sustainability, continuity and achievement of long-lasting competitive results in sport. In the efforts to create additional values for sport organizations, a proposal was made to apply the processes of knowledge creation, codification, sharing and transfer of knowledge, as well as its utilization in the efforts to achieve sport goals.